DI UNIT PPA SAT RESKRIM DALAM KEBERHASILAN DIVERSI PADA TINDAK PIDANA YANG DILAKUKAN OLEH ANAK ( Studi wilayah hukum Polda Sumatera Barat ) - Amran, Ridho Oktoviama; A. Khana, Philips; Fitriati, Fitriati (UNES Journal of Swara Justisia, 2019)
Article 7 of Law Number 11 Year 2012 on the Child Criminal Justice System Requires that the realization of Justice Restorative Justice by Diversi Process shall be pursued at the level of investigation, prosecution or in court. At the level of investigation in the police effort to realize the Diversi is not separated from the role of an investigator who will be a Mediator in Diversi. The purpose of this writing is to analyze the success rate of female investigators in realizing Diversi. Based on the research result, it can be concluded that female investigators are more effective in realizing the Diversity process in the children's case and prioritizing Justice Restorative Justice, so according to the data obtained in the field the success rate of female investigators is higher than the male investigators in realizing the settlement of the children's case against the law and the Third , in the Diversity Process on solving a child's case a female investigator is a good mediator, meaning that the female investigator as a mediator is not decided but merely as a liaison for more targeted communication and mitigate the negative impacts that occur to focus on the form of a solution that benefits both parties, because female investigators are more patient in understanding the characteristics of the two disputants, understanding the importance of all important parties to realize the full extent possible of Justice's restorative settlement.